Why do women with early breast cancer in Northern Sri Lanka undergo mastectomy? Decision-making and ways forward - Chrishanthi Rajasooriyar; Ramya Kumar; Dhivya Thuseetharan; Gopikha Sivakumar; Suman Muthulingam; Sutharshan Vengadasalam (BMC, 2024)
Abstract Background Despite robust evidence confirming equivalent survival rates and better cosmetic outcomes with breast-conserving surgery (BCS) and radiotherapy compared to mastectomy, the rates of mastectomy among women with early breast cancer have not declined significantly in Sri Lanka. This study explores views on the surgical treatment of breast cancer among Northern Sri Lankan women who were eligible for BCS but underwent mastectomy. Methods An exploratory descriptive qualitative study was carried out among 15 women who underwent mastectomy for early breast cancer. Patients who were referred to the Tellippalai Trail Cancer Hospital for adjuvant therapy after mastectomy and matched the study criteria were recruited. Data were collected through in-depth semi-structured interviews, which were transcribed in Tamil, translated into English, coded using QDA Miner Lite software, and analysed thematically. Results Nine out of 15 participants were either not aware of breast-conserving surgery (BCS) as a treatment option or their eligibility for BCS at the time of mastectomy. According to participant narratives, the treating team had recommended mastectomy to most participants. While many opted for mastectomy believing that it was associated with lower rates of recurrence and spread compared to BCS, these beliefs were frequently reinforced by the treating team. The pros and cons of the two approaches had not been discussed before surgery with most participants. In the absence of information, family and friends weighed in on the decision to opt for mastectomy, ultimately resulting in feelings of loss and regret in most instances. Conclusion Most participants were not aware that they were eligible for BCS. These information gaps need to be urgently addressed for women to make informed decisions about their health.